6y=3y-12

Simple and best practice solution for 6y=3y-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y=3y-12 equation:


Simplifying
6y = 3y + -12

Reorder the terms:
6y = -12 + 3y

Solving
6y = -12 + 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.
6y + -3y = -12 + 3y + -3y

Combine like terms: 6y + -3y = 3y
3y = -12 + 3y + -3y

Combine like terms: 3y + -3y = 0
3y = -12 + 0
3y = -12

Divide each side by '3'.
y = -4

Simplifying
y = -4

See similar equations:

| 7x^4-6x^2y^2-y^4=0 | | 6b+1=-47 | | -2n-3=-27 | | -6k+1=-41 | | -5t+1=-4 | | 3a-8=-29 | | 2(1/3w+1/4)=4+1/3w | | 32.3x+27.7=194.3 | | x^4y^2+13x^3y^3+22x^2y^4=0 | | 4+7d=-10 | | 2t+3=25 | | 6b-4=-58 | | 4d+7=43 | | -2k-3=15 | | 19s=171 | | x^2-24x-27=0 | | 19s=17 | | -5a-2=-62 | | 3t+2=5 | | 10+4m=58 | | 6a-5=-5 | | 5-5b=-40 | | 7k+5=54 | | 2t-6=-18 | | -4n+6=-10 | | -2+6t=-44 | | -8-3k=-8 | | 7a+1=8 | | 10x^4-5x^3y-75x^2y^2=0 | | -21=9a-15-13a | | -3y-4(8y+6)=8+8(7-y) | | 7/12d+3=-1/6d |

Equations solver categories